Screening and novel diagnostic technologies for melanoma: an update - Jonathan C. Hwang; Bryan L. Peacker; Rebecca I. Hartman (Melanoma Management, 2025)
Melanoma incidence has increased over recent decades, yet mortality has been relatively stable. This pattern has raised concern that many newly diagnosed melanomas, particularly melanoma in situ, may reflect overdiagnosis rather than a true increase in disease burden. Screening can detect melanoma earlier but is likely associated with overdiagnosis and overdetection, which may lead to excess morbidity with little survival benefit. This review examines global trends in melanoma incidence and mortality, the effects of screening programs, and the consequences of overdiagnosis. We evaluate both population-based and risk-directed screening strategies and assess diagnostic tools such as dermoscopy, total body photography, and artificial intelligence devices. Further research is needed to determine how these adjunctive technologies can be effectively integrated into screening strategies to improve clinical outcomes.